2021
DOI: 10.21608/fumj.2021.183655
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effect of Maternal Anemia on Fetal Doppler Indices and estimated fetal weight during the Last trimester of pregnancy in rural and suburban area

Abstract: Background: Anemia is an important global health problem affecting nearly 529 million women of reproductive age, including 38% of all pregnant women. Anemia during pregnancy is a key contributor to maternal mortality and poor birth outcomes in both low-and high-income countries. Reducing maternal anemia is widely recognized as central to the health of women and children. Current WHO global targets call for a 50% reduction of anemia in women of reproductive age by 2025. Maternal anemia is a hypoxic condition th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…The MCA pulsatility index in the non-anaemic group ranged from 1.35 to 1.70, in the mild anaemia group ranged from 1.21 to 1.64, in the moderate anaemia group ranged from 1.12 to 1.56 and in the severe anaemia group ranged from 0.98 to 1.51. The decrease in MCA PI in our study was significant ( P < 0.05) and corroborated well with the findings of Abdel Megeed AM et al [ 9 ], Ali et al [ 10 ] and Abdel Samie[ 5 ] et al The results also showed a decreasing trend of MCA PI with the severity of anaemia.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The MCA pulsatility index in the non-anaemic group ranged from 1.35 to 1.70, in the mild anaemia group ranged from 1.21 to 1.64, in the moderate anaemia group ranged from 1.12 to 1.56 and in the severe anaemia group ranged from 0.98 to 1.51. The decrease in MCA PI in our study was significant ( P < 0.05) and corroborated well with the findings of Abdel Megeed AM et al [ 9 ], Ali et al [ 10 ] and Abdel Samie[ 5 ] et al The results also showed a decreasing trend of MCA PI with the severity of anaemia.…”
Section: Discussionsupporting
confidence: 92%
“…Mean UmA PI values in all groups showed a statistically significant increase ( P < 0.05) with the increasing severity of anaemia. Similar results were seen in a study done by Abdel Samie AS et al [ 5 ] with mean UmA PI higher in the severe anaemia group at 1.11 ± 0.27 than the mild or moderate anaemia groups ( P < 0.000). Studies done by Mohamad Ihab Md et al ,[ 6 ] Ghada A et al [ 7 ] and Rafiq S et al [ 8 ] showed similar results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation